2016
DOI: 10.1016/j.jinteco.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Imported inputs and invoicing currency choice: Theory and evidence from UK transaction data

Abstract: A signi…cant proportion of international trade is in intermediate goods. This paper considers theoretically and empirically how exporters' dependence on imported inputs a¤ects their choice of invoicing currency. The model predicts that exporters that depend more on foreign currency-denominated inputs are less likely to price in their home currency. I test this and other theoretical results using a novel dataset that covers UK trade transactions with non-EU countries. I …nd considerable support for the model's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 37 publications
(45 reference statements)
3
50
0
Order By: Relevance
“…The first microeconomic determinant brought up in works of Novy (2006); Goldberg & Tille (2008b); Chung (2015) is the intra-firm hedging behavior. Firms that use imported inputs use more non-domestic currencies than the ones that produce only from domestic resources.…”
Section: Micro Determinantsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first microeconomic determinant brought up in works of Novy (2006); Goldberg & Tille (2008b); Chung (2015) is the intra-firm hedging behavior. Firms that use imported inputs use more non-domestic currencies than the ones that produce only from domestic resources.…”
Section: Micro Determinantsmentioning
confidence: 99%
“…The closest research to this paper would be the papers by Chung (2015) and (Devereux et al , 2015). The former concentrates on the role of intermediate inputs in firm-level currency choice, the latter asks a question how market shares of the firms -both the exporters and importers effects the exchange rate pass through and choice of currency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies found that firms with past experiences in exporting also tend to initiate importing activities, because particular sunk costs are shared between importing and exporting. This literature may also include Amiti, Itskhoki, and Konings () and Chung (). Although the former study examined the relationship between import intensity and exchange rate pass‐through in exporting, the latter revealed that exporters' dependence on imported inputs affects their choice of invoice currency when exporting.…”
Section: Introductionmentioning
confidence: 99%